Kontekstualisasi Injil Dalam Etnis Tionghoa Di Pesaren Bangka - Daniel Abdi (Sekolah Tinggi Teologi Simpson Ungaran, 2022)
The development of local culture and beliefs greatly impacted the spread of the Gospel. In serving the mission, understanding the concept of local culture and beliefs will bring contextualization to the cultural enculturation that has existed hundreds of years ago at Bangka Islamic Boarding School. The cultural tradition of respecting the Lord of the sky, the Lord of the earth and the Lord of mankind, namely the deceased ancestors (Tian Di Akung) is the influence of Confucianism which is the central subject of Chinese cultural beliefs in Pesaren. Human efforts in the search for salvation have been maintained from generation to generation. But in the Christian faith salvation is a gift from the Lord Jesus Christ, and the concept of justification from the creator is accepted as a central subject of evangelism.Â Â